2012
DOI: 10.4081/jlimnol.2012.e1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological effects of multiple stressors on a deep lake (Lago Maggiore, Italy) integrating neo and palaeolimnological approaches

Abstract: To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 89 publications
4
26
0
Order By: Relevance
“…, 2009), because Si reflects both siliciclastic matter and biogenic components. Low values of Si/Al in sediment unit I reflect low biogenic silica contents, proven by diatom counts in core LM 1b, and therefore a low internal productivity, which is in good agreement with limnological data (Guilizzoni et al. , 2012).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…, 2009), because Si reflects both siliciclastic matter and biogenic components. Low values of Si/Al in sediment unit I reflect low biogenic silica contents, proven by diatom counts in core LM 1b, and therefore a low internal productivity, which is in good agreement with limnological data (Guilizzoni et al. , 2012).…”
Section: Resultssupporting
confidence: 84%
“…3). The generally darker colour of sediment unit II is attributable to increased organic material as indicated by an increase in loss on ignition and total carbon in core LM 1b (Guilizzoni et al. , 2012) as well as higher abundances of diatom frustules observed in thin sections and determined in core LM 1b by Guilizzoni et al.…”
Section: Resultsmentioning
confidence: 99%
“…Birks & Birks, ; Davidson et al ., ; Michelutti & Smol, ). However, with few notable exceptions (Birks & Birks, ; Sayer et al ., ; Guilizzoni et al ., ), rarely have such studies been conducted on as large a number of biological groups as here, most involving a mix of physical and chemical proxies with just one or two biological groups included to infer broader environmental change. Of course, handling data from several fossil groups and multiple cores is not straightforward, but the approach taken here, where plant and animal macrofossil data are amalgamated from three cores, has proved successful in revealing a strong sequence of events and coherent patterns which are consistent with botanical records from the site (Davidson et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous palaeoecological studies have examined one or more of these fossil groups to assess ecological response to eutrophication (e.g. Leavitt et al ., ; Miskimmin, Leavitt & Schindler, ; Brooks, Bennion & Birks, ; Taylor et al ., ; Sayer et al ., ; Guilizzoni et al ., ; Hobbs et al ., ). However, the potential of the fuller sediment record for assessing food‐web alterations and interactions between the various components of shallow lake ecosystems, over long timescales, is yet to be fully explored.…”
Section: Introductionmentioning
confidence: 97%
“…One of the biggest problems in these areas which are affected by climate change is the quality and quantity of water resources supplied to the growing population (Pouliotte et al ., ). Numerous studies have demonstrated that climate changes have significant effects on water temperature (Dokulil et al ., ; Schneider, 2009; Hetherington et al ., ) and lake ecosystems (Verburg and Hecky, ; Guilizzoni et al ., ). Lake and reservoir water temperature is sensitive to meteorological variables.…”
Section: Introductionmentioning
confidence: 97%